La noix de coco - Dossier du mois - Gerbaud, P.; Audibert, O.; Bourdeix, Roland (Centre de coopération internationale en recherche agronomique pour le développement, 2011)
Like passion fruit, coconuts are much better known in processed form than fresh. The processing industry has long focused on this tropical fruit that is rich in flavour and can be used in many ways whereas sales of fresh nuts are smaller in term of volume. More than other fruits, coconuts are found in extremely varied forms, not only in the food industry but also in sectors such as cosmetics, building and pharmaceuticals. Sales of fresh coconuts are marginal but growing on the European markets. They have a strongly exotic image but are difficult to use, reducing retail sales. A number of innovations to reducing the obstacle of shelling could stimulate consumption in the future.